Pendidikan Islam dan Perubahan Sosial di Indonesia: Kajian Fungsionalisme Atas Peran Kebijakan dalam Menjaga Solidaritas Sosial - Maratus Shalihah; Nur Khasanah (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This study aims to analyze how Islamic education policy in Indonesia functions as a social mechanism in shaping and maintaining societal integration amidst modern social change. Based on Émile Durkheim's functionalism theory, this study views Islamic education as an institution that plays a vital role in maintaining moral order, social solidarity, and preventing symptoms of anomie resulting from an imbalance between traditional values and the demands of modernity. The approach used is qualitative with an exploratory-descriptive orientation, with data collection techniques through literature studies of policy documents, institutional reports, and related scientific research results. The analysis is conducted descriptively and analytically to interpret the social function of the policy based on the concepts of social solidarity, division of labor, and anomie. The results show that policies such as madrasah integration, religious moderation programs, and teacher professionalization have a manifest function in expanding access to education, increasing social mobility, strengthening gender equality, and strengthening cohesion between religious communities. However, latent functions are also found in the form of bureaucratization of educational institutions, resource inequality, and value resistance among local communities. These findings confirm that Islamic education policy operates ambivalently: as an integrative instrument that strengthens social solidarity, but also as an arena for value negotiation between tradition and modernity. Therefore, Islamic education policy needs to be directed in a more contextual and participatory manner to optimally function as an agent of inclusive, adaptive, and sustainable social transformation for modern Indonesian society.